Participation Motivation Scale For E-Sports: Validity and Reliability Study (PMSES) - Oğuzhan Gül; Mehmet Gül; Recep Uzun (Türk Spor ve Egzersiz Dergisi)
Electronic sports appeared in the world in the late 1970s and gained popularity in the 2000s.  In Turkey, on the other hand, the popularity and the number of players have increased after 2008. In this study, the Participation Motivation Scale for E-Sports (PMSES) was developed in order to evaluate the motivation for participation of those who do E-Sports. The research included 590 participants that play various E-Sports games. The research was designed as the structural equation and mixed model. Within the scope of the structural validity of the scale, exploratory factor analysis (EFA) was carried out in the SPSS 23, and confirmatory factor analysis (CFA) was applied to the measuring instrument in AMOS Software. The Kaiser-Meyer-Olkin (KMO) value was found to be 0.975 and the sample size was found to be sufficient. As a result of the factor analysis applied regarding the validity of the scale, three factors representing 78.847% of the total variance were obtained. The Cronbach Alpha coefficient was calculated as 0.972 as a result of the reliability analysis of the 22-item scale. It can be said that the Participation Motivation Scale for E-Sports (PMSES) is a valid and reliable data collection tool that can measure the participation motivation of the individuals who do E-Sports.